2011
DOI: 10.1108/01443571111172435
|View full text |Cite
|
Sign up to set email alerts
|

Project portfolio selection in continuous improvement

Abstract: Purpose -The purpose of this paper is to provide a systematic overview of approaches to project portfolio selection in continuous improvement and to identify opportunities for future research. Design/methodology/approach -This paper reviews the extant literature on the theory and application of project portfolio selection in continuous improvement. Findings -Manufacturing organisations must routinely deliver efficiencies in order to compete, but their ability to realise sustainable competitive advantage from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 105 publications
0
31
0
2
Order By: Relevance
“…There are hundreds of business improvement initiatives that organisations can use, with examples including lean management, six sigma, Business Process Reengineering (BPR), Balanced Scorecard, Quality Management Systems, Total Quality Management (TQM) and performance benchmarking (Kornfeld and Kara 2011, Greasley 2004, Psomas, Fotopoulos, and Kafetzopoulos 2011, Yung and Chan 2003. This study examines the differences in levels of awareness, use and effectiveness of improvement initiatives in different countries and by organisations of different characteristics such as size and industry sector.…”
Section: Introductionmentioning
confidence: 99%
“…There are hundreds of business improvement initiatives that organisations can use, with examples including lean management, six sigma, Business Process Reengineering (BPR), Balanced Scorecard, Quality Management Systems, Total Quality Management (TQM) and performance benchmarking (Kornfeld and Kara 2011, Greasley 2004, Psomas, Fotopoulos, and Kafetzopoulos 2011, Yung and Chan 2003. This study examines the differences in levels of awareness, use and effectiveness of improvement initiatives in different countries and by organisations of different characteristics such as size and industry sector.…”
Section: Introductionmentioning
confidence: 99%
“…A number of academic studies (Yung and Chan 2003, Greasley 2004, Kornfeld and Kara 2011, Psomas, Fotopoulos, and Kafetzopoulos 2011 and consultancy based studies (Rigby and Bilodeau 2013) have shown the extensive use of improvement tools and techniques, the most popular typically being benchmarking, business excellence, knowledge management, Plan, Do, Check, Act (PDCA), Quality Function Deployment (QFD), Six Sigma and Total Quality Management (TQM). The literature also highlights that organisations in different sectors and industries are likely to place different emphasise when selecting which improvement tools and techniques to implement (Rees 1995).…”
Section: Introductionmentioning
confidence: 99%
“…VPM is a new technology, without documented best practices in contemporary literature, especially for integration models (Kornfeld & Kara, 2011). A lack of literature on virtual project innovation and strategies, coupled with the significance of each topic associated for implementing best practices was the deciding factor for sselection of six research topics.…”
Section: Purposementioning
confidence: 99%
“…There was a significant lack of literature on virtual project team integration (Bullen & Love, 2011;Kornfeld & Kara, 2011). VPM is a new technology, without documented best practices in contemporary literature, especially for integration models (Kornfeld & Kara, 2011).…”
Section: Purposementioning
confidence: 99%